Towards an ethics of enjoyment in (geriatric) care Eine Ethik des Genusses in der Pflege älterer und hochaltriger Menschen - Arndt, Megan; Teuchert, Lisanne (Ethik in der Medizin, 2024)
Definition of the problem: Enjoyment has not yet played a significant role in ethical approaches to (geriatric) care. Rather, the focus of ethical considerations is often on questions of self-reliance and autonomy. Relevant topics are skills loss issues and how to deal with them. Although it is very important to allow grief in the context of the need for care and of aging, the question remains: in how far could an ethics of enjoyment help to set a further focus on questions of relish. Argumentation and sources: Philosophical and theological approaches such as those of Emmanuel Lévinas, Ina Praetorius and Corine Pelluchon show the fundamental importance of corporeality, being nourished and enjoyment. Also, moments of sensual indulgence are valued as meaningful by nursing staff and by persons cared for. These moments can be part of professional care but also happen in situations that go beyond nursing activity in the narrower sense. Moments of enjoyment are interrelated with livability, happiness and health but cannot be fully functionalized. Conclusion: An ethics of enjoyment based on these approaches can enrich the perception of care and the theoretical and empirical study of care. This article offers an ethical introduction into the topic and a draft of an ethics of enjoyment in theses.
CRIS-Team Scopus Importer:2024-09-30
Keywords: Enjoyment; Ethics of care; Old age; Relish; Sensuality